Interacción social e interacción discursiva de un canal de YouTube educativo - John ANZOLA-GOMEZ,Dra. Diana RIVERA-ROGEL,Dr. Ignacio AGUADED (Fonseca, Journal of Communication, 2023)
YouTube is a social network that represents web development as it is a space where anyone can publish audiovisual content and where the user can generate different types of interaction. In the educational field, the interaction between teacher and student is essential for the teaching-learning process development, so the analysis of communicative interactions in digital environments such as YouTube is necessary.